The divine and demoniac :Mahisa's heroic struggle with Durga - Berkson, Carmel (Oxford University Press, 1995)
This is a remarkable study of the contemporary power of a myth whose origins can be traced back to the ancient civilizations of Europe, Egypt, Mesopotamia, and South Asia. The author views the myth as a significant reflection of the tension between the adolescent male, striving for a separate identity, and the dominating mother figure, filtered through the consciousness of the Brahmin priest/myth maker/narrator.